2019
DOI: 10.1155/2019/8632701
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Microbial Colonization Patterns in Central Venous Catheters, 2013–2017

Abstract: Objectives. This study was performed to provide epidemiological information on microbial colonization in central venous catheters (CVCs). Methods. CVCs submitted to Medical Microbiology Laboratory from January 1, 2013, through October 1, 2017, which met our criteria would be included for analysis. Quantitative culture was used for CVCs. The results of culture and related information on CVCs were collected and recorded in detail. The prevalence was calculated, and related factors were analyzed statistically. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…In consistence with the international CLABSI pathogen distribution patterns available from numerous studies, causative microorganisms typically originate from the normal resident flora of the skin present at the insertion site, which are mostly consisting by gram-positives such as Staphylococcus spp, Streptococcus spp., Corynebacterium spp., and Candida spp. [22][23][24].However, later studies and data from our previous survey, support that CLABSIs caused by Gram-negatives either predominated in the panel of isolated organisms or exhibited growing trends [25][26][27]. In our study the epidemiology profile of CLABSI pathogens reflects the recently published Greek ICU pathogen profile, where MDR A. baumannii is frequently isolated [28].…”
Section: Gram Positive Bacteriasupporting
confidence: 75%
“…In consistence with the international CLABSI pathogen distribution patterns available from numerous studies, causative microorganisms typically originate from the normal resident flora of the skin present at the insertion site, which are mostly consisting by gram-positives such as Staphylococcus spp, Streptococcus spp., Corynebacterium spp., and Candida spp. [22][23][24].However, later studies and data from our previous survey, support that CLABSIs caused by Gram-negatives either predominated in the panel of isolated organisms or exhibited growing trends [25][26][27]. In our study the epidemiology profile of CLABSI pathogens reflects the recently published Greek ICU pathogen profile, where MDR A. baumannii is frequently isolated [28].…”
Section: Gram Positive Bacteriasupporting
confidence: 75%
“…Based on the international reports on CLABSI pathogen epidemiology available from numerous studies, causative microorganisms typically originate from the normal resident flora of the skin present at the insertion site, which are mostly consisting by gram-positives such as coagulase-negative staphylococci, and Corynebacterium spp [18][19][20]. However, previous studies report a change in CLABSI pathogen profile, with Gram-negatives either predominating in the panel of isolated organisms or displaying increasing trends [21][22][23]. This change in the types of pathogens could be attributed to the broad implementation of infection control programs targeting Gram-positive organisms [24].…”
Section: Discussionmentioning
confidence: 99%
“…The literature has reported conflicting data regarding the risk of catheter infection for the three venous sites of catheterization. Most studies have indicated a higher risk at the femoral site and a lower risk at the subclavian site [15] [16] [17], whereas others have reported no difference [8] DOI: 10.4236/aid.2022.122023 292 Advances in Infectious Diseases [18] [19]. Many clinical practice guidelines have suggested that the femoral site should be avoided because of an anticipated higher risk of catheter-associated bloodstream infection; nonetheless, the preferred site for insertion is complex and depends on the skills of the operator.…”
Section: Discussionmentioning
confidence: 99%